The π-conjugation length determines the fluorescence quenching mechanism of aromatic aldehydes in water - Fletcher, Katharyn M.; Krämer, Maximilian; Bunz, Uwe H. F.; Dreuw, Andreas (Chemical physics, 2018)
Water-soluble distyrylbenzene-based aldehydes are excellent fluorescence turn-on indicators for amine detection, since they are themselves non-fluorescent in water. Here, the fluorescence quenching mechanisms of aldehydes with systematically increasing π-systems are investigated in an aqueous environment using quantum chemical methods. Although the aldehydes are structurally related, with each extension of the π-system the fluorescence quenching mechanism changes from excited-state hydrogen transfer to trans→cis isomerization and nπ∗ state-mediated intersystem crossing, until the aldehydes become fluorescent in water. For distyrylbenzene aldehyde, nπ∗ mediated ISC has been identified as major fluorescence quenching channel, which becomes closed upon reaction with an amine explaining its fluorescence turn-on sensitivity.
Gesehen am 22.04.2020